MENYONGSONG 25 TAHUN SISTER CITY JAKARTA – TOKYO - Witarsa Tambunan (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractThe term sister city was originally introduced by Dwight Eisehower to the XII century,which means the town brothers, friendly city. The concept of sister city intends to maximizethe relationship between community members in all corners of the world to be created andmaintain peace. Sister city Jakarta - Tokyo has succeeded in building a positive image ofJakarta as an international city. As an international city, Jakarta has a vision of